2015
DOI: 10.1177/1098611115584910
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 13-Hour 20-Minute Work Shifts on Law Enforcement Officers' Sleep, Cognitive Abilities, Health, Quality of Life, and Work Performance

Abstract: To determine the impact of a longer-than-average compressed workweek on police officers’ sleep, cognitive abilities, health, quality of life, and work performance, two precincts of the Phoenix Police Department participated in a 9-month, repeated-measures study. The experimental precinct worked three consecutive 13-hr 20-min (13:20-hr) shifts per week for 6 months, while the control precinct worked four 10-hr shifts per week. Officers were assessed using the Pittsburgh Sleep Quality Index, Psychomotor Vigilanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…Three studies addressed both sleepiness and fatigue directly. Overall sleep quality and fatigue were of great concern in the study from Bell et al 51 ) ; officers working the longer shift experienced significant decreases in hours of sleep, sleep quality, concentration, cognitive processing and quality of life. The same group also experienced significant increases in fatigue, daytime dysfunction, reaction time, anticipatory errors and complaints.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Three studies addressed both sleepiness and fatigue directly. Overall sleep quality and fatigue were of great concern in the study from Bell et al 51 ) ; officers working the longer shift experienced significant decreases in hours of sleep, sleep quality, concentration, cognitive processing and quality of life. The same group also experienced significant increases in fatigue, daytime dysfunction, reaction time, anticipatory errors and complaints.…”
Section: Discussionmentioning
confidence: 95%
“…The same group also experienced significant increases in fatigue, daytime dysfunction, reaction time, anticipatory errors and complaints. Most interestingly, upon returning to their regular 10 h shifts (for two months), all variables returned to pre-study levels, and officers overwhelmingly preferred the 10 h shift system51 ) . Similarly, Elliott and Lal43 ) also found poor sleep quality and fatigue severity was pervasive in the police officers working 12 h shifts.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It is not possible to eliminate shift work in this occupation, but education on proper sleep hygiene along with research on the appropriate lengths of various shifts may improve officer health. For example, Bell, Verdin, Lewis, and Cassidy (2015) found that officers working three consecutive 13 hour 20 minute (13:20) shifts per week suffered from more fatigue, sleepiness, and cognitive processing problems than officers working four 10-hour shifts. Amendola, Weisburd, Hamilton, Jones, and Slipka (2011) found that officers working10-hour shifts had a significantly higher quality of work life and averaged significantly more sleep than those officers working 8- or 12-hour shifts.…”
Section: Discussionmentioning
confidence: 99%
“…Fatigue resulting from unpredictable or extended working hours is a factor that negatively impacts the performance of police officers (Bell et al 2015;Houdmont and Randall 2016;Scholarios et al 2017). However, the impact of fatigue on officer performance during police interviews with children is as yet unknown.…”
Section: Introductionmentioning
confidence: 99%